2007
DOI: 10.2337/db06-1506
|View full text |Cite
|
Sign up to set email alerts
|

Omentin Plasma Levels and Gene Expression Are Decreased in Obesity

Abstract: Central obesity and the accumulation of visceral fat are risk factors for the development of type 2 diabetes and cardiovascular disease. Omentin is a protein expressed and secreted from visceral but not subcutaneous adipose tissue that increases insulin sensitivity in human adipocytes. To determine the impact of obesity-dependent insulin resistance on the regulation of two omentin isoforms, gene expression and plasma levels were measured in lean, overweight, and obese subjects. Omentin 1 was shown to be the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
524
14
32

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 658 publications
(636 citation statements)
references
References 47 publications
(43 reference statements)
43
524
14
32
Order By: Relevance
“…A previous report showed that gender difference is observed in circulating omentin concentration. 7 It has also been shown that carotid IMT is generally greater in men than in women. 14 Although it is well established that plaque thickness is a predictor of cardiovascular risk, 12 no plaque in carotid artery was observed in apparently healthy subjects in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report showed that gender difference is observed in circulating omentin concentration. 7 It has also been shown that carotid IMT is generally greater in men than in women. 14 Although it is well established that plaque thickness is a predictor of cardiovascular risk, 12 no plaque in carotid artery was observed in apparently healthy subjects in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Omentin is detectable in human plasma and is downregulated in subjects with obesity and type 2 diabetes. 7,8 Low levels of plasma omentin are also associated with insulin resistance and endothelial dysfunction. 9,10 Thus, it is conceivable that circulating omentin is associated with obesity-linked disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Omentin-1 is a newly identified depot-specific adipokine in human adipose tissue that may modulate insulin sensitivity by its paracrine or endocrine functions [13].It was shown that omentin-1 levels were inversely correlated with measures of obesity and insulin resistance and positively correlated with adiponectin levels [15]. It was also reported that omentin-1 levels were lower in patients with metabolic syndrome than in controls [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, omentin-1 enhances insulin action and Akt phosphorylation [14]; it is inversely related to obesity [15] and is down regulated by insulin and glucose [13]. In an in vitro study to investigate the effects of omentin-1 on bone metabolism, omentin-1 reduced osteoclast formation by stimulating OPG and inhibiting RANKL production in osteoblasts [16].…”
Section: Introductionmentioning
confidence: 99%
“…32 Plasma levels of Intelectin 1 are inversely correlated with BMI, waist circumference and insulin resistance. 33 A study that investigated association of Val109Asp variant of ITLN1 with type 2 diabetes in Caucasians failed to detect the same. 34 On contrary, our analysis revealed association of rs1333062 in 3¢ flank region of ITLN1, which is in complete LD with Val109Asp of ITLN1 (D¢¼1.0 and r 2 ¼1.0 both for GIH (Gujarati Indians in Houston, Texas) and CEU (Utah residents with Northern and Western European ancestry from the CEPH collection) populations from HapMap data).…”
Section: Resultsmentioning
confidence: 99%